Methods to Kill Hostages or Kidnapped Persons - T. V. Bilyk (Bulletin of Kharkiv National University of Internal Affairs)
Scientific opinions, as well as forensic and investigative practice on the peculiarities of the method of killing hostages or kidnapped persons have been analyzed. The content of the structure of murder methods within the system of forensic characteristics of crimes against human life and health has been revealed. The author has analyzed the essence and has revealed the concept of the method of killing hostages or kidnapped persons; the author has also analyzed its main elements.